HUBUNGAN PERILAKU CAMAT DENGAN KINERJA PEGAWAI DI KANTOR CAMAT KELAM PERMAI KABUPATEN SINTANG - Antonius Tony Segah E.42008031 (FISIP Universitas Tanjungpura Pontianak, 2013)
This study aimed to determine and analyze the performance of the behavioral relationships with employees in Head Office Kelam Permai Sintang district. Study were selected because of the phenomenon and the problems that arise as a result of the attitude of the lack of ability as a district leader associated with employee performance as indicated by the decline in the performance of employees at Head Office Kelam Permai. This is indicated by the lack of discipline in the District Office where the scenic office employee doing unproductive activities, ie reading newspapers and watching television, reading newspapers, and talking among fellow employees. This is of course related to many factors, but the authors have alleged temporary factors that leader behavior will improve employee performance as much as possible in the Head Office Kelam Permai.The conclusion of this study is the behavior of sub-district has a significant influence on the performance of employees at 45.9% and the remaining 54.1% is influenced by other factors not examined such as motivation, communication, working environment or other variables.Keywords: Behavioral Leadership, Employee Performance.